Speech-ABRs in cochlear implant recipients: feasibility study. (3rd October 2019) - BinKhamis, Ghada; Perugia, Emanuele; O'Driscoll, Martin; Kluk, Karolina
Abstract: Objective: The aim of this study was to assess the feasibility of recording speech-ABRs from cochlear implant (CI) recipients, and to remove the artefact using a clinically applicable single-channel approach. Design: Speech-ABRs were recorded to a 40 ms [da] presented via loudspeaker using a two-channel electrode montage. Additionally, artefacts were recorded using an artificial-head incorporating a MED-EL CI with stimulation parameters as similar as possible to those of three MED-EL participants. A single-channel artefact removal technique was applied to all responses. Study sample: A total of 12 adult CI recipients (6 Cochlear Nucleus and 6 MED-EL CIs). Results: Responses differed according to the CI type, artefact removal resulted in responses containing speech-ARB characteristics in two MED-EL CI participants; however, it was not possible to verify whether these were true responses or were modulated by artefacts, and artefact removal was successful from the artificial-head recordings. Conclusions: This is the first study that attempted to record speech-ABRs from CI recipients. Results suggest that there is a potential for application of a single-channel approach to artefact removal. However, a more robust and adaptive approach to artefact removal that includes a method to verify true responses is needed.